The narrative of success. The strategy of humanization in neoliberal film creation - Galindo Pérez, José María (2024)
This paper aims to analyze several specific forms of filmmaking very related to neoliberalism as an economic, political and cultural system, taking as reference the affective turn to explore this link. For this, it will be considered the different contributions that, from different fields of social sciences, have linked the evolution of capitalism with the conquest of the sphere of affections and emotions, and it will use the methodology of film analysis to verify, in a set of concrete works, the features of that relationship. From this intersection between theoretical proposals and case analysis, the article wants to show an expressive strategy based on the humanization of certain behaviors, through the cinematographic narrative, which normalizes some attitudes and values ​​due to decisions which work on the construction of the story an the aesthetics of the work. This strategy will be verified in three very significant films: The Social Network, Steve Jobs and The Founder.